2022
DOI: 10.1021/acsomega.1c06898
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Sm3+ and Er3+ Cations on the Structural, Optical, and Magnetic Traits of Spinel Cobalt Ferrite Nanoparticles: Comparison Investigation

Abstract: In this study, we investigated a comparison of the structure, morphology, optic, and magnetic (room temperature (RT)) features of Er3+ and Sm3+ codoped CoFe2O4 (CoErSm) nanospinel ferrite (NSFs) (x ≤ 0.05) synthesized via hydrothermal (H-CoErSm NSFs) and sonochemical (S-CoErSm NSFs) approaches. The formation of all products via both synthesis methods has been validated by X-ray powder diffraction (XRD) and scanning electron microscopy (SEM), along with energy-dispersive X-ray (EDX) and transmission electron mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 37 publications
0
31
0
Order By: Relevance
“…Magnetic nanoparticles are known to exist in multimagnetic domain structures if the squareness ratio is greater than or equal to 0.5. For a sample with x = 0.000 to 0.075, the squareness ratio is less than 0.5, indicating that they are single-domain structures . Whereas the sample with x = 0.100 has a higher value of squareness ratio, meaning it has multimagnetic domains.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Magnetic nanoparticles are known to exist in multimagnetic domain structures if the squareness ratio is greater than or equal to 0.5. For a sample with x = 0.000 to 0.075, the squareness ratio is less than 0.5, indicating that they are single-domain structures . Whereas the sample with x = 0.100 has a higher value of squareness ratio, meaning it has multimagnetic domains.…”
Section: Resultsmentioning
confidence: 96%
“…Rare-earth substitution (Gd 3+ , Dy 3+ , Er 3+ , etc.) in cobalt ferrite is extensively studied due to the highly interesting and tunable magnetic properties of the resulting materials. , However, for intrinsic and substituted/doped nanoferrites, the properties and performance characteristics are significantly affected by the particle size, size distribution, and cation distribution at A- and B-sites in the crystal structure. , Even a slight change in the method of synthesis and/or processing parameters along with precursor chemicals in the synthesis can result in variability in microstructure, crystal chemistry, and material properties. , For instance, Aziz et al showed comparisons of the properties of Dy 3+ -substituted cobalt ferrite between ultrasonication using ethanol and dry grinding, and the properties of magnetic materials changed . Thus, as evident from the literature, the degree of inversion depends on heat treatment, synthesis method, concentration, and nature of substituted ions. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,[9][10][11][12][13] Moreover, from the previous literature, Slimani et al reported the inuence of Sm 3+ and Er 3+ doping on the CoFe 2 O 4 system and found that saturation magnetization increases with an increase in doping concentrations. 14 Additionally, the anisotropydependent magnetic coercive eld is probably affected by the dopant concentration. However, when La 3+ and Y 3+ ions are both substituted in nano spinel ferrites, it will change the coercivity and magnetic anisotropy in an enhanced manner, as suggested by Almessiere et al 15 Among these, Eu-doped Fe 3 O 4 MNPs draw signicant attention, predominantly in clinical experimentations, due to the negligible toxicity of Eu 3+ and its unique magnetic and optical properties.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15][16][17][18][19] The structural, magnetic, and MCE properties of COF can be tuned by doping/substituting divalent or trivalent cations. 11,[18][19][20][21][22][23][24] The tunability of structural parameters due to Cr 3+ substitution in stoichiometric and non-stoichiometric COF is reported in our earlier literature. 25 It was observed that there are structural defects due to Cr 3+ substitution.…”
Section: Introductionmentioning
confidence: 99%